Calpain-1 weakens the nuclear envelope and promotes the release of neutrophil extracellular traps - Singh, Jeeshan; Zlatar, Leticija; Munoz Becerra, Marco; Lochnit, Günter; Herrmann, Irmgard; Pfister, Felix; Janko, Christina; Knopf, Jasmin; Leppkes, Moritz; Schoen, Janina; Munoz, Luis Enrique; Schett, Georg; et al. (Cell Communication and Signaling, 2024)
The inducers of neutrophil extracellular trap (NET) formation are heterogeneous and consequently, there is no specific pathway or signature molecule indispensable for NET formation. But certain events such as histone modification, chromatin decondensation, nuclear envelope breakdown, and NET release are ubiquitous. During NET formation, neutrophils drastically rearrange their cytoplasmic, granular and nuclear content. Yet, the exact mechanism for decoding each step during NET formation still remains elusive. Here, we investigated the mechanism of nuclear envelope breakdown during NET formation. Immunofluorescence microscopic evaluation revealed a gradual disintegration of outer nuclear membrane protein nesprin-1 and alterations in nuclear morphology during NET formation. MALDI-TOF analysis of NETs that had been generated by various inducers detected the accumulation of nesprin-1 fragments. This suggests that nesprin-1 degradation occurs before NET release. In the presence of a calpain-1, inhibitor nesprin-1 degradation was decreased in calcium driven NET formation. Microscopic evaluation confirmed that the disintegration of the lamin B receptor (LBR) and the collapse of the actin cytoskeleton occurs in early and later phases of NET release, respectively. We conclude that the calpain-1 degrades nesprin-1, orchestrates the weakening of the nuclear membrane, contributes to LBR disintegration, and promoting DNA release and finally, NETs formation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Calpain-1; Nesprin-1; Neutrophil extracellular traps (NETs); Nuclear envelope break down

Hypoxia Promotes Neutrophil Survival After Acute Myocardial Infarction - Dölling, Maximilian; Eckstein, Markus; Singh, Jeeshan; Schoen, Janina; Shan, Xiaomei; Bozec, Aline; Knopf, Jasmin; Schett, Georg; Munoz Becerra, Luis; Herrmann, Martin; Schauer, Christine (Frontiers in Immunology, 2022)
Phagocytosis, degranulation, and neutrophil extracellular traps (NETs) formation build the armory of neutrophils for the first line of defense against invading pathogens. All these processes are modulated by the microenvironment including tonicity, pH and oxygen levels. Here we investigated the neutrophil infiltration in cardiac tissue autopsy samples of patients with acute myocardial infarction (AMI) and compared these with tissues from patients with sepsis, endocarditis, dermal inflammation, abscesses and diseases with prominent neutrophil infiltration. We observed many neutrophils infiltrating the heart muscle after myocardial infarction. Most of these had viable morphology and only few showed signs of nuclear de-condensation, a hallmark of early NET formation. The abundance of NETs was the lowest in acute myocardial infarction when compared to other examined diseases. Since cardiac oxygen supply is abruptly abrogated in acute myocardial infarction, we hypothesized that the resulting tissue hypoxia increased the longevity of the neutrophils. Indeed, the viable cells showed increased nuclear hypoxia inducible factor-1α (HIF-1α) content, and only neutrophils with low HIF-1α started the process of NET formation (chromatin de-condensation and nuclear swelling). Prolonged neutrophil survival, increased oxidative burst and reduced NETs formation were reproduced under low oxygen tensions and by HIF-1α stabilization in vitro. We conclude that nuclear HIF-1α is associated with prolonged neutrophil survival and enhanced oxidative stress in hypoxic areas of AMI.
CRIS-Team Scopus Importer:2022-03-04
Keywords: acute myocardial infarction; DNA decondensation; hypoxia inducible factor 1; NET formation; neutrophil extracellular traps; neutrophils

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Neutrophil Extracellular Trap-Borne Elastase Prevents Inflammatory Relapse in Intercritical Gout - Liu, Lei; Shan, Lizhen; Wang, Han; Schauer, Christine; Schoen, Janina; Zhu, Lingjiang; Lu, Ci; Wang, Zitao; Xue, Yu; Wu, Huaxiang; Herrmann, Martin (Arthritis and Rheumatology, 2023)
Objective. Gout flares that occur during urate-lowering therapy (ULT) are typically related to the shrinkage of tophi due to aggregated neutrophil extracellular traps (NETs) that have captured monosodium urate crystals in the tissues. The present study was undertaken to analyze the blocking effect of alpha(1)-antitrypsin on neutrophil elastase, and it was found that alpha(1)-antitrypsin induced rapid inflammation in the presence of unstable tophi.
CRIS-Team WoS Importer:2023-05-19

Neutrophil extracellular traps and DNases orchestrate formation of peritoneal adhesions. - Elrod, Julia; Heuer, Annika; Knopf, Jasmin; Schoen, Janina; Schönfeld, Lavinia; Trochimiuk, Magdalena; Stiel, Carolin; Appl, Birgit; Raluy, Laia Pagerols; Saygi, Ceren; Zlatar, Leticija; Hosari, Sami; et al. (iScience, 2023)
Peritoneal adhesions are poorly understood but highly prevalent conditions that can cause intestinal obstruction and pelvic pain requiring surgery. While there is consensus that stress-induced inflammation triggers peritoneal adhesions, the molecular processes of their formation still remain elusive. We performed murine models and analyzed human samples to monitor the formation of adhesions and the treatment with DNases. Various molecular analyses were used to evaluate the adhesions. The experimental peritoneal adhesions of the murine models and biopsy material from humans are largely based on neutrophil extracellular traps (NETs). Treatment with DNASE1 (Dornase alfa) and the human DNASE1L3 analog (NTR-10), significantly reduced peritoneal adhesions in experimental models. We conclude that NETs serve as essential scaffold for the formation of adhesions; DNases interfere with this process. Herein, we show that therapeutic application of DNases can be employed to prevent the formation of murine peritoneal adhesions. If this can be translated into the human situation requires clinical studies.
EVALuna2:551953

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

Neutrophils’ Extracellular Trap Mechanisms: From Physiology to Pathology - Schoen, Janina; Euler, Maximilien; Schauer, Christine; Schett, Georg; Herrmann, Martin; Knopf, Jasmin; Yaykasli, Kürsat Oguz (International Journal of Molecular Sciences, 2022)
Neutrophils are an essential part of the innate immune system and the first line of defense against invading pathogens. They phagocytose, release granular contents, produce reactive oxygen species, and form neutrophil extracellular traps (NETs) to fight pathogens. With the characterization of NETs and their components, neutrophils were identified as players of the innate adaptive crosstalk. This has placed NETs at the center not only of physiological but also pathological processes. Aside from their role in pathogen uptake and clearance, NETs have been demonstrated to contribute to the resolution of inflammation by forming aggregated NETs able to degrade inflammatory mediators. On the other hand, NETs have the potential to foster severe pathological conditions. When homeostasis is disrupted, they occlude vessels and ducts, serve as sources of autoantigens and danger or damage associated molecular patterns, directly damage tissues, and exaggerate complement activity and inflammation. This review focusses on the understanding of NETs from their formation to their functions in both physiological and pathological processes.
CRIS-Team Scopus Importer:2022-11-25
Keywords: aggNETs; autoantigens; DAMP; inflammation resolution; neutrophil extracellular traps; occlusions

Neutrophils Orchestrate the Periodontal Pocket - Vitkov, Ljubomir; Munoz Becerra, Luis; Schoen, Janina; Knopf, Jasmin; Schauer, Christine; Minnich, Bernd; Herrmann, Martin; Hannig, Matthias (Frontiers in Immunology, 2021)
The subgingival biofilm attached to tooth surfaces triggers and maintains periodontitis. Previously, late-onset periodontitis has been considered a consequence of dysbiosis and a resultant polymicrobial disruption of host homeostasis. However, a multitude of studies did not show “healthy” oral microbiota pattern, but a high diversity depending on culture, diets, regional differences, age, social state etc. These findings relativise the aetiological role of the dysbiosis in periodontitis. Furthermore, many late-onset periodontitis traits cannot be explained by dysbiosis; e.g. age-relatedness, attenuation by anti-ageing therapy, neutrophil hyper-responsiveness, and microbiota shifting by dysregulated immunity, yet point to the crucial role of dysregulated immunity and neutrophils in particular. Furthermore, patients with neutropenia and neutrophil defects inevitably develop early-onset periodontitis. Intra-gingivally injecting lipopolysaccharide (LPS) alone causes an exaggerated neutrophil response sufficient to precipitate experimental periodontitis. Vice versa to the surplus of LPS, the increased neutrophil responsiveness characteristic for late-onset periodontitis can effectuate gingiva damage likewise. The exaggerated neutrophil extracellular trap (NET) response in late-onset periodontitis is blameable for damage of gingival barrier, its penetration by bacteria and pathogen-associated molecular patterns (PAMPs) as well as stimulation of Th17 cells, resulting in further neutrophil activation. This identifies the dysregulated immunity as the main contributor to periodontal disease.
CRIS-Team Scopus Importer:2021-12-17
Keywords: bacterial membrane vesicles; caspase 11; caspase 4; dysbiosis; dysregulated immunity; NET formation; outer membrane vesicles

Periodontitis-Derived Dark-NETs in Severe Covid-19 - Vitkov, Ljubomir; Knopf, Jasmin; Krunić, Jelena; Schoen, Janina; Minnich, Bernd; Hannig, Matthias; Herrmann, Martin; Schauer, Christine (Frontiers in Immunology, 2022)
The frequent severe COVID-19 course in patients with periodontitis suggests a link of the aetiopathogenesis of both diseases. The formation of intravascular neutrophil extracellular traps (NETs) is crucial to the pathogenesis of severe COVID-19. Periodontitis is characterised by an increased level of circulating NETs, a propensity for increased NET formation, delayed NET clearance and low-grade endotoxemia (LGE). The latter has an enormous impact on innate immunity and susceptibility to infection with SARS-CoV-2. LPS binds the SARS-CoV-2 spike protein and this complex, which is more active than unbound LPS, precipitates massive NET formation. Thus, circulating NET formation is the common denominator in both COVID-19 and periodontitis and other diseases with low-grade endotoxemia like diabetes, obesity and cardiovascular diseases (CVD) also increase the risk to develop severe COVID-19. Here we discuss the role of propensity for increased NET formation, DNase I deficiency and low-grade endotoxaemia in periodontitis as aggravating factors for the severe course of COVID-19 and possible strategies for the diminution of increased levels of circulating periodontitis-derived NETs in COVID-19 with periodontitis comorbidity.
CRIS-Team Scopus Importer:2022-05-06
Keywords: dysregulated immunity; inhibition of NET formation; NET hyper-responsiveness; NET-induced damage; neutrophil hyper-responsiveness; trained immunity

Synthetic biology and the possibilities in achieving a plant demand and soil buffer capacity adapted nitrogen (n) recycling - Schorr, Lena; Schoen, Janina; Benckiser, Gero (Soil and Recycling Management in the Anthropocene Era, 2021)
The world demand for nitrogen (N) fertilizer increases since Haber and Bosch’s invention of technical nitrogen fixation (TNF) with an average growth of 1.9% per annum or an amount of 117.116 tons N in 2019 (FAO in World Fertilizer Trends and Outlook to 2020, 2017, [34]). Landscapes not only receive TNF, but also the wastes from industrial livestock farming, an increasing industrialisation, a growing population and from overloading wastewater treatment plants by the production of sewage sludge. Thus, the administration is forced to handle and for instance the German capital Berlin hired 14.364 ha land in 1913 and installed a sewage farm for spreading Berlin’s wastewater. In 1926, the amount of heavy-metal polluted wastewater produced by Berlin’s industry was 7.3%. In 1988, still 34% of all accruing wastewater was spread on the fields [61]. From Berlin’s nutrient over satiated sewage farm soil, alarming amounts of nitrate flew into nearby glacial valley wells, surface waters and riverbank filtrates, which are used as drinking water sources and thus, in 1988 the wastewater spreading on the sewage farm stopped. Synthetic biology is a promising approach to reduce soil N buffer capacity over satiating concentrations. The possibilities of synthetic biology techniques in the focus of this chapter are discussed towards curing N recycling related impacts on health, soil management and wasterwater treatment plants.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Anammox; Chassis organisms; Dinitrification; Nitrification; Nitrogen pollution; Nitrogen recycling; Soil and wasterwater management; Synthetic biology